Evaluation of assessment in the context of work‐based learning: Qualitative perspectives of new graduates. Issue 2 (28th July 2014) - Palermo, Claire; Chung, Alexandra; Beck, Eleanor J.; Ash, Susan; Capra, Sandra; Truby, Helen; Jolly, Brian
Abstract Aim Evaluation or assessment of competence is an important step to ensure the safety and efficacy of health professionals, including dietitians. Most competency‐based assessment studies are focused on valid and reliable methods of assessment for the preparation of entry‐level dietitians, few papers have explored student dietitians' perceptions of these evaluations. The present study aimed to explore the perceptions of recent graduates from accredited nutrition and dietetics training programs in Australia. It also aimed to establish the relevance of competency‐based assessment to adequately prepare them for entry‐level work roles. Methods A purposive sample of newly graduated dietitians with a range of assessment experiences and varied employment areas was recruited. A qualitative approach, using in‐depth interviews with 13 graduates, was undertaken. Graduates were asked to reflect upon their competency‐based assessment experiences as a student. Data were thematically analysed by multiple authors. Results Four themes emerged from the data analysis: (i) transparency and consistency are critical elements of work‐based competency assessment; (ii) students are willing to take greater responsibility in the assessment process; (iii) work‐based competency assessment prepares students for employment; and (iv) the relationship between students and their assessors impacts student experience and assessment performance. Conclusions Understanding this unique perspective of students can improve evaluation of future health professionals and assist in validating competency‐based assessment approaches.